A systematic X-ray study of the dwarf novae observed with Suzaku. (22nd December 2016) - Wada, Qazuya; Tsujimoto, Masahiro; Ebisawa, Ken; Hayashi, Takayuki
Abstract : X-ray behavior of the dwarf novae (DNe) outside the quiescent state has not been fully understood. We thus assembled 21 data sets of the 15 DNe observed by the Suzaku satellite by the end of 2013, which include spectra taken during not only the quiescence, but also the transitional, outburst, and super-outburst states. Starting with the traditional cooling flow model to explain the X-ray emission from the boundary layer, we made several modifications to account for the observed spectra. As a result, we found that the best-fitting spectral model depends strongly on the state of the DNe with only a few exceptions. Spectra in the quiescent state are explained by the cooling flow model plus a Fe fluorescent line emission attenuated by an interstellar extinction. Spectra in the transitional state require an additional partial covering extinction. Spectra in the outburst and super-outburst state require additional low-temperature thin-thermal plasma component(s). Spectra in the super-outburst state further require a high value of minimum temperature for the boundary layer. We present an interpretation on the required modifications to the cooling flow model for each state.